Interlayer properties of tungsten fibre-reinforced composites and their determination by different methods. (September 2021) - Gietl, H.; Riesch, J.; Zielinski, M.; Höschen, T.; Coenen, J.W.; Schönen, S.; Neu, R.
Abstract: Tungsten features a unique combination of properties which makes it a candidate for the use as a plasma-facing material in fusion reactors. The main drawbacks of tungsten are its brittleness at moderate temperature and the susceptibility to embrittlement during operation. To overcome this limitations tungsten fibre-reinforced tungsten composites (Wf /W) have been developed. The interlayer between the tungsten fibre and tungsten matrix enables the activation of extrinsic mechanisms to improve the toughness similar to ceramic fibre-reinforced ceramics. In addition, the evaluation of the interlayer parameter is a necessary for the efforts to model the composite behaviour. Therefore, single fibre model systems with Er 2 O 3 and Y 2 O 3 as interlayer were evaluated by push-out and pull-out tests. The results were used to determine the interfacial shear strength ( τ d e b ), the interfacial frictional shear stress ( τ f r ) and the fracture energy of the interlayer ( Γ i ). In addition, tensile tests on the composite material were performed to evaluate the interfacial frictional shear stress. The evaluation methods were critically discussed as the results show that the influence of the evaluation method is larger than the actual tested interlayer material. Graphical abstract: Highlights: Evaluation of the interlayer properties of W f /W with three different methods. The interlayer testing method has a larger influence on the evaluated values than the actual tested interlayer material. For the further material screening pull-out test is preferred over push-out test for W f /W.